E-learning and higher education: Understanding and supporting organisational change in New Zealand - Stephen Marshall (Flexible Learning Association of New Zealand, 2012)
Over an 18 month period four educational institutions, a New Zealand University, PTE (Private Tertiary Enterprise), Wānanga, and ITP (Institute of Technology or Polytechnic), have engaged in a process of change influenced by technology. Their e-learning capability was benchmarked using the e-learning Maturity Model (eMM) and this information used to stimulate change activities. The project has worked with the staff of participating institutions to understand and support the explicit and implicit processes used to change and improve the e-learning experiences of students and staff. The resulting case studies, discussed in this paper, illustrate the issues that face tertiary organisations and leaders engaging with the opportunities and challenges of e-learning. Five factors have been identified as significant influences on the ability of organisations to change in response to technology in the current political and educational landscape of the New Zealand tertiary sector.